Isolation of female germline stem cells from porcine ovarian tissue and differentiation into oocyte-like cells - Huy-Hoang NGUYEN; Bui Le Quynh NHU; Nguyen Nhat Phuong UYEN; Van-Thuan NGUYEN; Hong-Thuy BUI (The Society for Reproduction and Development, 2019)
Historically, it had been widely accepted that the female mammalian ovary contained a limited number of oocytes that would reduce over time, without the possibility of replenishment. However, recent studies have suggested that female germline stem cells (FGSCs) could replenish the oocyte-pool in adults. The aim of this study was to isolate FGSCs from porcine ovaries and differentiate them into oocyte-like cells (OLCs). The FGSCs were successfully isolated from porcine ovarian tissue and cultured in vitro, in DMEM/F-12 medium supplemented with growth factors (EGF, FGF, GDNF, etc.) and a supplement (N21). These cells possessed spherical morphology and expressed specific germline characteristics (Vasa, Stella, Oct4, c-kit). By evaluating different conditions for in vitro differentiation of FGSCs, co-culturing the isolated FGSCs with MEF cells, under three-dimensional (3D) cell cultures, were shown to be optimal. FGSCs could successfully be differentiated into OLCs and reached about 70 µm in diameter, with a large number of surrounding somatic cells. Importantly, OLCs contained large nuclei, about 25-30 µm, with filamentous chromatin, similar to oocyte morphology, and expressed oocyte-specific markers (Gdf9, Zp2, SCP3, etc.) at the same level as oocytes. In conclusion, we successfully isolated FGSCs from porcine ovarian tissue and differentiated them into oocyte-like cells. This will provide a valuable model for studying a new, alternative source of oocytes.